Bird identification and conservation in Semarang Traditional Markets, Indonesia - HUSNA’ PUTRI NUR ‘AZIZAH; IFFAH NABILA; KHARISMA DAMAYANTI; IKHLASUL AQMAL KHAWARIZMI; MUCHAMMAD SHOLIQIN; MUHAMMAD INDRAWAN; TITI WAHYUNI; JOHAN ISKANDAR; AHMAD DWI SETYAWAN (Smujo International, 2025)
Abstract. Nur ‘Azizah HP, Nabila I, Damayanti K, Khawarizmi IA, Sholiqin M, Indrawan M, Wahyuni T, Iskandar J, Setyawan AD. 2025. Bird identification and conservation in Semarang Traditional Markets, Indonesia. Nusantara Bioscience 17: 103-117. Birds are one of the wildlife species that humans widely utilize as food, pets, economic resources, and for their aesthetic value. Bird markets in Indonesia have become an integral part of people's lives, but this can also be a threat if not properly controlled. The objectives of this study were to identify bird species traded in bird markets, assess their selling prices, analyze the conservation status and endemicity of traded species, and evaluate the sustainability of bird markets. This research was conducted in three traditional markets in Central Java Province, Indonesia, i.e., (i) Banyuputih Market in Salatiga City; (ii) Pasar Pon Ambarawa in Semarang District; and (iii) Kartini Market in Semarang City, using a descriptive qualitative method with a survey and observation approach. The collected data were grouped based on several categories, such as the type of bird species, conservation status, and the location where the species was found. The results of this study showed 46 families with 136 bird species, of which 18 species are non-endemic and 118 species are endemic. Based on the conservation status, according to IUCN, several species are rare (23 species), namely endangered (9 species), vulnerable (3 species) and near threatened (11 species); as well as 13 species are included in Appendix II of CITES; and 14 species are nationally protected according to Permen LHK No.P.20/2018. Most birds come from wild hunting (106 sp.) instead of breeding (30 sp.). Two endemic bird species, including rare according to the three institutions, are Pycnonotus cyaniventris (cucak kelabu) and P. zeylanicus (cucak rawa). Suppliers and traders need to pay attention to the sustainability of the bird trade through biological conservation by providing more breeding birds. Efforts are needed to apply the principles of sustainable development that include economic, social, and environmental aspects in the bird trade in bird markets.